The mechanical properties of graphene reinforced polystyrene - Nur Zakirah, Kasnan (2017)
Industrial needs and technological advancement drives the demand for lighter materials, resistant and is durable, has flexibility with viable cost. Thus arose polymeric composites with different types of use and application to know; aeronautics, aerospace, automobile and sporting goods. Development of polymer nanocomposite is an interesting area in advanced material research because of its capability of providing improved mechanical, thermal and electrical properties. In comparison to other materials the potential use of graphene based nanocomposites has attracted wide attention both for fundamental aspects as well as applications. The challenges for development high performance graphene polystyrene nanocomposites are to ensure good quality dispersion of graphene in the polymer matrix. This paper presents mechanical properties studies of graphene and polystyrene nanocomposite. Different compositions of graphene and polystyrene mixture were manufactured by using melt blending technique. The mechanical properties of GPS nanocomposites were studied through tensile, flexural and impact tests. X-ray diffraction (XRD) was employed to characterize the formation of nanocomposites. Moderate improvement of impact energy was found up to 22% which proved that GPS nanocomposites were successfully toughened by graphene. Addition of graphene to polystyrene also increases the tensile strength significantly. Moreover, the modulus strength also had increases with additional of graphene. The result express of stiffness and strength of the material. Reduction of flexural modulus demonstrated modifier was better in maintaining the stiffness while enhancing the toughness of PS. XRD established that Graphene were well dispersed and preferentially embedded in the PS phase. Formulation of 98.5:1.5 polystyrene to graphene ratio was shown the balance portion between stiffness and toughness of the GPS nanocomposite. The GPS nanocomposite is believed to offer possibilities can be used in automotive and furniture applications.